Effect of Bleaching on Surface Roughness of Universal Composite Resins After Chlorhexidine-Induced Staining - Gözde Aksoy Vaizoğlu (Dentistry Journal, 2025)
Objective: The aim of this study was to compare the surface roughness of a conventional composite resin, a one-shade universal composite resin, and a group-shade universal composite resin after bleaching. Methods: A conventional composite resin, Clearfill, and the universal composite resins Omnichroma and Optishade were prepared into discs (2 × 8 mm), with a total of 90 discs. Each group (30) contained three different groups, including a control (n10), coloured with CHX (n10), and after bleaching (n10). The surface roughness of group discs was measured with a 3D profilometer. ANOVA and Kruskal–Wallis Tests were used to analyse data. Analyses were performed in the SPSS programme. Results: Significant Ra values were obtained between subgroups (p < 0.05). Comparisons of surface roughness after discolouring were performed with the control group; the highest surface roughness value (p > 0.05) was found for Optishade after bleaching compared to the control group. The Optishade composite resin showed the highest initial surface roughness value (p > 0.05), and after discolouration followed by bleaching, the Clearfill composite resin showed the highest surface roughness value (p > 0.05). Conclusions: Both immersion and bleaching applications cause surface roughness. As a result, it was determined that the composite resin content has a significant effect on the surface roughness in discolouring and bleaching processes.